Penerapan Hukum Acara dalam Penyelesaian Sengketa di Pengadilan: : (Studi Kasus Tindak Pidana Narkotika di Pengadilan Negeri Binjai) - Siti Zahra Siagian; Parlaungan G. Siahaan; Dewi Pika L. Batu; Alissa Putri Simbolon; Devi Permata Br. Bangun; Seevaira Chyta Simanullang (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to analyze the application of criminal procedural law in resolving narcotics crime cases at the Binjai District Court, focusing on compliance with the due process of law principle and the protection of the defendant’s rights. The research employs an empirical juridical approach through direct observation (field research) of case Number 200/Pid.Sus/2025/PN Bnj involving the defendant Novri Syahputra, who was charged as an intermediary in the sale and purchase of Class I narcotics (methamphetamine) weighing 40.81 grams net. Data were collected through direct observation of the trial proceedings and examination of relevant legal documents, including the Criminal Procedure Code (KUHAP) and Law No. 35 of 2009 on Narcotics. The findings indicate that the implementation of procedural law at the Binjai District Court was consistent with the provisions of KUHAP, covering all stages from the reading of the indictment, witness examination, evidence presentation, to the final judgment. The panel of judges demonstrated professionalism and independence while considering both aggravating and mitigating factors. However, rehabilitative and humanistic approaches have not been fully incorporated into the court’s consideration, as the sentencing remains predominantly deterrent-oriented. The study concludes that, while the formal procedural aspects of criminal procedural law have been effectively implemented, there remains a substantive need to strengthen restorative and rehabilitative justice values in future narcotics case policies.